Hak dan kewajiban warga negara Indonesia - Azizi, Azmi `Aly (Maliki Interdisciplinary Journal, 2026)
The rights and obligations of Indonesian citizens are fundamental pillars in national life. Although the 1945 Constitution provides a clear legal framework, implementation in practice still faces challenges such as unequal access to basic rights, weak law enforcement, and low public awareness of civic duties. This study employs a qualitative approach with descriptive analysis of legal literature, public policy, and socio-political dynamics influencing the implementation of citizens’ rights and obligations. Findings indicate that despite the availability of constitutional norms, there remains a significant gap between legal provisions and societal practice. Contributing factors include social, political, and economic developments, as well as globalization, which demand policy adaptation. To address these challenges, comprehensive strategies are required, including strengthening civic education, enhancing public policy transparency, and ensuring consistent law enforcement. These measures will enable citizens’ rights and obligations to function in balance and effectively support the sustainability of national life.